'Bottom of the Pyramid Innovation' and Pro-Poor Growth - Kaplinsky, Raphael (World Bank, Washington, DC, 2017)
Outside of China, despite rapid economic growth in many low and middle income countries, there has been little progress in meeting the MDG1 target of halving the incidence of global poverty by 2014. Part of the explanation for this weak poverty-reducing performance has been the historic trajectory of innovation. During the 20th Century, most of global innovation had its origins in the north, producing products for high income consumers, developing technologies which excluded poor producers and technologies which were energy intensive and polluting. This innovation trajectory gave rise to the not-for-profit Appropriate Technology movement after the 1970s. But many of the technologies which they it were inefficient and were scorned by both producers and consumers. However a series of disruptive factors the growth of low income consumers in the context of global economic slowdown, the development of radical technologies (such as mobile telephony and renewable power), the development of capabilities in low income economies and the emergence of new types of innovation actors have begun to transform the potential of AT to support pro-poor growth. Whilst this new vintage of ATs will be largely market-driven (since it provides the potential for profitable production), there are important dimensions in which this market-driven process can be supported by policy.